Spatialities and Artistries of Crisis: Towards Reinvention in Sara Baume’s A Line Made by Walking (2017) - Bourdeau, Marion (Intermédialités / Intermediality, 2025)
This article focuses on Sara Baume’s 2017 novel A Line Made by Walking and analyses the sensitive, artistic, and intermedial reinvention of its protagonist’s intimate landscapes in a time of crisis. It assesses the uncertain nature of the spatialities at hand, interrogates the representations and practices of the Anthropocene, and examines the role of artistic multimodality and intermediality as agents of (re)mediation and reinvention.